If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 = 2 + -5(9 + -1x) 27 = 2 + (9 * -5 + -1x * -5) 27 = 2 + (-45 + 5x) Combine like terms: 2 + -45 = -43 27 = -43 + 5x Solving 27 = -43 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 27 + -5x = -43 + 5x + -5x Combine like terms: 5x + -5x = 0 27 + -5x = -43 + 0 27 + -5x = -43 Add '-27' to each side of the equation. 27 + -27 + -5x = -43 + -27 Combine like terms: 27 + -27 = 0 0 + -5x = -43 + -27 -5x = -43 + -27 Combine like terms: -43 + -27 = -70 -5x = -70 Divide each side by '-5'. x = 14 Simplifying x = 14
| 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) | | 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 | | 7(9+-2x)=9(7x-2) | | 16x^2-11x+26=0 | | 9c-36= | | (x+y)dx+(x-y)dy=0 | | 7(5-4)+3x=4(x+2) | | -13-7x=9x-11 | | 12x+7=-4x+9 | | -15=-5y | | 8x+4/2=4x-2/3 | | 15/3-7x=9+5x |